Advancing sea turtle conservation in the South China Sea via U.S.‐China diplomacy. Issue 5 (12th April 2021) - Yeh, Frederick C.; Lin, Liu; Zhang, Ting; Green, Robin; Martin, Frances; Shi, Haitao
Abstract: The South China Sea is an important oceanic habitat for endangered sea turtles, which are facing anthropogenic pressures from the illegal wildlife trade, fisheries by‐catch, debris pollution, habitat loss, and climate change. Compounding these threats are international disputes over territorial claims in the South China Sea, exerting a general disinclination toward regional collaborations to solve environmental issues. Since sea turtles are migratory animals that move through aquatic and terrestrial habitats, feeding in waters, and nesting on beaches under the jurisdiction of multiple countries, the species is an ideal ambassador to raise public support for international collaborations. Transnational communications to coordinate conservation efforts across borders provide a positive agenda of cooperation to build trust, creating a politically neutral platform to facilitate opportunities for diplomacy to reset and improve foreign relations, underscoring the value of sea turtles as a flagship species to reduce international tensions and bring nations together. For this reason, the U.S.‐China EcoPartnership between Sea Turtles 911 and Hainan Normal University was formed to empower local communities to protect the ocean through sea turtle rescue, public education, and scientific research projects. Genetic research determined the geographic origins of illegally traded sea turtles, validating the uniqueness of the Paracel (Xisha) Islands rookery, and urging policymakers to establish a large‐scale sea turtle nature reserve in the South China Sea. To define boundaries of the proposed marine protected area, sea turtles were tracked with satellite telemetry delineating their migratory routes and habitats across multiple countries, underscoring the importance of international collaborations. Debris pollution survey at a major turtle nesting beach in the Paracel Islands demonstrated that pollution is negatively impacting newborn turtle hatchlings and that regional cooperation in the South China Sea should promote the reduction and cleanup of marine debris. Laparoscopic surgery was performed on sea turtles for the first time in China to assess the gender ratio of the local population, which revealed a female biased ratio, indicative of the effects of climate change. A sea turtle rescue center was jointly established in which more than 100 sea turtles were successfully rescued and released by the international and local community, including students who won national awards for their volunteer service. Implementing grassroots initiatives for sea turtle conservation have become an ideal diplomatic channel to strengthen U.S.‐China relations as several diplomats, including U.S. Ambassador Max Baucus, have engaged in people‐to‐people exchanges during public educational events. This international partnership serves as a case example in which current political disputes can be set aside to prepare future generations for the existential threat of biodiversity loss and climate change, while increasing peace, stability, and turtles in the region.